Perilaku Pemilihan Makanan dan Pengenalan Anggota Koloni pada Semut Rangrang Oecophylla smaragdina: Food Preference and Nestmate Recognition of Weaver Ants Oecophylla smaragdina - Hasan, M. Ubaidilah; Fitradiansyah, La Ode Fitradiansyah; Susanti, Fera Susanti; Raffiudin, Rika (Departemen Biologi, Institut Pertanian Bogor, 2021)
Weaver ants Oecophylla smaragdina are social insects that recognize nestmates using pheromone. This study analyzes the feeding behavior and nestmate recognition of weaver ants in the urban area of three different islands (Sumatra: Baturaja; Java: Banyuwangi; Papua: Sorong). The free ants were placed in the arena composed of chicken meat, sugar, bananas as the baits. Ten trapped ants were also located in the arena to explore the nestmate recognition between the free and the trapped ants. Five types of behaviors, i.e., approach, stalking, communication, competition, and agonistic, were recorded in 6 days. Food preferences were indicated by the number of conduct towards the feeding sites, and nestmate recognition was indicated by approaching the trapped nestmate. The results showed that the percentage of the approach behavior of free ants was the highest in the three islands but had no significant difference between Sumatra and Java and between Java and Sorong (p-value >0.05). However, the study showed significant differences for the other four behaviors observed. As predicted, the percentage of chicken meat foraged by the ants was the highest due to the carnivorous behavior. The free ants showed the nestmate recognition to the trapped ants in all behavior, except competition.